2008
DOI: 10.1111/j.1468-2982.2008.01550.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Grey Matter Changes in Patients With Migraine: A Voxel-Based Morphometry Study

Abstract: We used voxel-based morphometry (VBM) to compare grey matter volume (GMV) between 20 migraine patients (five with aura and 15 without aura) with normal conventional magnetic resonance imaging findings and 33 healthy controls matched for age and sex. A separate analysis was also performed to delineate a possible correlation between the GMV changes and the headache duration or lifetime headache frequency. When compared with controls, migraine patients had significant GMV reductions in the bilateral insula, motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
236
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(272 citation statements)
references
References 35 publications
32
236
2
2
Order By: Relevance
“…Indeed, there is growing recent evidence showing that chronic neuropathic pain is associated with changes in brain structure. Several volumetric studies have shown that neuropathic pain is associated with changes in the thalamus, nucleus accumbens, and insular, posterior parietal, cingulate, and dorsolateral prefrontal cortices (Apkarian et al, 2004;Kuchinad et al, 2007;Buckalew et al, 2008;DaSilva et al, 2008;Kim et al, 2008). Furthermore, using diffusion tensor imaging, we have shown previously that neuropathic pain after complete spinal cord injury is associated with structural alterations in the VP thalamus, nucleus accumbens, ventral pons, and posterior parietal, dorsolateral prefrontal, and medial orbitofrontal cortices (Gustin et al, 2010).…”
Section: Brain Anatomical Changes and Neuropathic Painmentioning
confidence: 68%
See 1 more Smart Citation
“…Indeed, there is growing recent evidence showing that chronic neuropathic pain is associated with changes in brain structure. Several volumetric studies have shown that neuropathic pain is associated with changes in the thalamus, nucleus accumbens, and insular, posterior parietal, cingulate, and dorsolateral prefrontal cortices (Apkarian et al, 2004;Kuchinad et al, 2007;Buckalew et al, 2008;DaSilva et al, 2008;Kim et al, 2008). Furthermore, using diffusion tensor imaging, we have shown previously that neuropathic pain after complete spinal cord injury is associated with structural alterations in the VP thalamus, nucleus accumbens, ventral pons, and posterior parietal, dorsolateral prefrontal, and medial orbitofrontal cortices (Gustin et al, 2010).…”
Section: Brain Anatomical Changes and Neuropathic Painmentioning
confidence: 68%
“…Although most chronic pain investigations have focused on peripheral targets such as nociceptors and their terminations, there is evidence that changes within higher brain centers may also be important for the maintenance and/or development of some chronic pain conditions. For example, many chronic pain conditions are associated with gray matter losses in a number of brain regions associated with acute pain processing, i.e., primary and secondary somatic areas, insula, thalamus, and cingulate cortex (Apkarian et al, 2004;Kuchinad et al, 2007;Schmidt-Wilcke et al, 2007;Buckalew et al, 2008;DaSilva et al, 2008;Kim et al, 2008;Schweinhardt et al, 2008;Burgmer et al, 2009;Gustin et al, 2010;Younger et al, 2010). Despite numerous investigations reporting brain anatomy changes associated with chronic pain, it remains unknown what these gray matter changes represent and whether these changes are uniformly expressed in all chronic pain conditions regardless of their etiology.…”
Section: Introductionmentioning
confidence: 99%
“…Altered activity, functional connectivity, and grey matter density of this brain structure have also been reported in migraineurs [60,69]. Indeed, migraineurs were identified to have structural and functional cerebral abnormalities in the prefrontal cortex, the rostral ACC, the somatosensory cortex, the orbitofrontal cortex, and insular cortex [70,71]. Migraineurs were found to have reduced cortical thickness in both the ACC and the insular cortex, another brain structure involved in processing the emotional component of pain.…”
Section: Anterior Cingulate Cortex In Pain and Rewardmentioning
confidence: 93%
“…New findings from extensive functional imaging studies on central pain networks allowed the identification of patterns of cortical and brainstem activation in some way ''specific'' for different primary headache subtypes [12][13][14]. In addition, structural alterations (either as hypertrophic or hypotrophic changes) of these areas have been consistently reported in headache series [15,16] as well as in other chronic pain syndromes [17][18][19] leading to the assumption that the repeated activation of the pain networks may promote neuroplastic cortical changes causing a permanent facilitation of pain signals, ultimately leading to the chronicisation of pain [20].…”
Section: Cortical Spreading Depression and Migrainementioning
confidence: 99%